1992
DOI: 10.1104/pp.100.2.762
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Curvature in Maize Roots by Calcium or by Thigmostimulation

Abstract: We examined the response of primary roots of maize (Zea mays L. cv Merit) to unilateral application of calcium with particular attention to the site of application, the dependence on growth rate, and possible contributions of thigmotropic stimulation during application. Unilateral application of agar to the root cap induced negative curvature whether or not the agar contained calcium. This apparent thigmotropic response was enhanced by including calcium in the agar. Curvature away from objects applied unilater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 18 publications
3
40
0
Order By: Relevance
“…Using Ca2+-specific microelectrodes, Bjorkman and Cleland (1991) found a distinct and differential gradient in the apoplastic Ca2+ activity between the upper and the lower side of gravistimulated maize (Zea mays L.) root tips that was required for gravitropism. These observations, in conjunction with the finding that asymmetric application of Ca2+ caused curvature toward the source (Ishikawa and Evans, 1992), provide indirect evidence that gravity-induced Ca2+ redistribution is necessary for gravitropic curvature. The development of this asymmetry in apoplastic Ca2+ may mediate growth control.…”
supporting
confidence: 55%
See 2 more Smart Citations
“…Using Ca2+-specific microelectrodes, Bjorkman and Cleland (1991) found a distinct and differential gradient in the apoplastic Ca2+ activity between the upper and the lower side of gravistimulated maize (Zea mays L.) root tips that was required for gravitropism. These observations, in conjunction with the finding that asymmetric application of Ca2+ caused curvature toward the source (Ishikawa and Evans, 1992), provide indirect evidence that gravity-induced Ca2+ redistribution is necessary for gravitropic curvature. The development of this asymmetry in apoplastic Ca2+ may mediate growth control.…”
supporting
confidence: 55%
“…However, the evidence has been indirect and sometimes contradictory. For example, unilateral application of Ca 2+ via agar blocks, which has often been cited as evidence for a role of Ca 2 + asymmetries in the root graviresponse, do not always lead to the same result (Hasenstein et al, 1988;Ishikawa and Evans, 1992;Takahashi et al, 1992). Ca 2< transport studies have shown the preferential polar transport of 45 Ca 2 ' toward the lower side of graviresponding maize roots (Lee et al, 1983b), but no asymmetry in free Ca 2+ between upper and lower sides of the roots could be detected (Dauwalder et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The length of this region thus represents about 5.5% of the entire growth zone. Subsequent studies confirmed the uniqueness of the cells located in the PIG zone, not only from a morphometrical point of view, but also on account of their specific cytological and physiological properties (Barlow et al, 1991;BaluSka et al, l992,1994BaluSka et al, l992, ,1996aBaluSka et al, l992, , 1996cIshikawa and Evans, 1992, 1993, 1995.…”
mentioning
confidence: 57%
“…51 A number of experimental data globally indicates that the transition zone of the root may be considered as a sort of sensory center, enabling the root apex to continuously monitor environment parameters and to trigger appropriate responses. [51][52][53][54][55][56][57][58][59][60][61][62][63] Future studies will be needed to deepen the role of this unique root zone in translating the external stimuli in motoric responses.…”
Section: The Root Transition Zonementioning
confidence: 99%